Analisa Kebijakan Publik Terhadap Pengelolaan Pasar Tradisional - Sofiani, Nancy; Saputra*, Tio; Syamsir, Syamsir; Frinaldi, Aldri (Universitas Syiah Kuala, 2023)
This study aims to determine the analysis of public policy on the management of traditional markets. Traditional market management policy is a form of public policy that regulates and oversees the management of traditional markets. The type of method used in this article is a literature review. Writing this literature review adopts national articles published on various platforms providing journals on a national scale that discuss public policy analysis of traditional market management. The research results show that the implementation of traditional market management policies can help create a healthier and more productive market environment for traders and visitors. However, this policy must also pay attention to the social, economic and environmental impacts that may arise and must constitute a target or objective of a government program, so that it is made at a higher level up to the technical level. Aims to increase the economic growth of the community. The expected result of these activities is the availability of economic facilities as a forum to move and grow the regional economy so that the community's economic activities can develop properly and open up employment opportunities